Charge critical sensors first: Minimize data loss in wireless rechargeable sensor networks - Tong Li; Tang Liu; Jian Peng; Feng Lin; Wenzheng Xu (International Journal of Distributed Sensor Networks)
In this article, we study the scheduling of a charging vehicle to replenish sensor energy in a large-scale wireless sensor network, by utilizing the novel wireless energy transfer technology. We note that existing studies do not treat different sensors in the network discriminatively and consider only how to charge as many sensors as possible before their energy expirations. However, there are some critical sensors in the network, so that many other sensors have no alternative routing paths to upload their sensing data to the base station if the critical sensors die. Therefore, the energy expiration of a critical sensor will result in that not only the sensor itself cannot continue its monitoring task, but also many other sensors cannot send their data during the dead period of the critical sensor. Then, the monitoring quality of the sensor network will significantly deteriorate due to the energy expirations of the critical sensor. Unlike existing studies, we take into account the impact of energy depletions of critical sensors and investigate a charging scheduling problem for sensor networks, which is to schedule a charging vehicle to replenish a set of to-be-charged sensors, such that not only the amount of lost data by dead sensors is minimized, but also the traveling cost of the vehicle for charging sensors is minimized, too. We then propose a novel algorithm for the problem. We finally compare the proposed algorithm with existing studies and simulation results show that the amount of lost data by the proposed algorithm is only about 50% of those by the existing studies, and the weighted sum of the amount of lost data and the vehicle travel distance is about 70% of those by the existing ones.